Potential roles of non-lymphocytic cells in the pathogenesis of IgG4-related disease - Cai, Shaozhe; Hu, Ziwei; Chen, Yu; Zhong, Jixin; Dong, Lingli (Frontiers in Immunology, 2022)
Studies have confirmed the involvement of a variety of lymphocyte subsets, including type 2 helper T lymphocytes (Th2) and IgG4+ B lymphocytes, in the pathogenesis of IgG4-related disease (IgG4-RD). Those lymphocytes contribute to the major pathogenetic features of IgG4-RD. However, they are not the only cellular components in the immunoinflammatory environment of this mysterious disease entity. Recent studies have suggested that various non-lymphocytic components, including macrophages and fibroblasts, may also play an important role in the pathogenetic process of IgG4-RD in terms of contributing to the chronic and complex progress of the disease. Therefore, the potential role of non-lymphocyte in the pathogenesis of IgG4-RD is worth discussing.